Peradaban Islam di Spanyol - Husnul Khatimah (UNIVERSITAS BONDOWOSO, 2021)
Before the advent of Islam, Spain was inhabited by various nations, including the Suevi and the Celts who were one family with the original inhabitants of England, Scotland and Ireland. Apart from these nations, the Cartaghe, Romans and Vandals also inhabited the land. With a background of political conflict, Governor Vandal invited the Arabs to flock to Andalusia to carry out an invasion through the command of Thariq bin Ziyad and at that time Islam recorded a victory. From then on, Spain was a very important center of Islamic civilizatio rivaling Baghdad in the East. The existence of Islam in a country known as the country of Matador has had a significant impact on various aspects, especially in the aspects of knowledge and technology. In fact, it is advances in science and technology that support the success of his political mission.